2013
DOI: 10.1007/s00158-013-0931-8
|View full text |Cite
|
Sign up to set email alerts
|

Isogeometric shape optimization in fluid mechanics

Abstract: Document Version Isogeometric Shape Optimization in Fluid MechanicsPeter Nørtoft · Jens Gravesen Abstract The subject of this work is numerical shape optimization in fluid mechanics, based on isogeometric analysis. The generic goal is to design the shape of a 2-dimensional flow domain to minimize some prescribed objective while satisfying given geometric constraints. As part of the design problem, the steady-state, incompressible Navier-Stokes equations, governing a laminar flow in the domain, must be solved. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Furthermore, Basilevs et al [2] and Scott et al [3] have already demonstrated the efficient usage of IGA in conjunction with T-splines technology [4,5]. Shape optimization, in the context of IGA, has been presented in various works as, e.g., in [6,7,8] for the 2D case and in [9] for the 3D case. In these works, the control points are directly used as shape optimization parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Basilevs et al [2] and Scott et al [3] have already demonstrated the efficient usage of IGA in conjunction with T-splines technology [4,5]. Shape optimization, in the context of IGA, has been presented in various works as, e.g., in [6,7,8] for the 2D case and in [9] for the 3D case. In these works, the control points are directly used as shape optimization parameters.…”
Section: Introductionmentioning
confidence: 99%
“…There exists, however, works in pertinent literature, e.g., Morino & Bernardini (2001) [38], where P T E is permitted to be a collocation point in the context of a an enhanced formulation that involves an additional integral equation resulting from taking the derivative of the potential Φ(P), P ∈ Ω, with respect to the normal of the wake and letting P → P T E . After solving (6) or (10), we can calculate the hydrofoil's pressure coefficient c p using Bernoulli's equation:…”
Section: Continuous and Discrete Formulation Of The Problemmentioning
confidence: 99%
“…Moreover, the idea of bridging the gap between Computer-Aided Design (CAD) and Analysis by the introduction of IsoGeometric Analysis (IGA) by Hughes et al (2005) [1], see also Cottrell et al (2009) [2], which directly uses analysis suitable geometric models from the CAD representation, can be efficiently exploited, especially in problems of shape optimization. Shape optimization in the context of IGA has been presented in various works, as e.g., Wall et al (2008) [3], Nagy et al (2009) [4], Nguyen et al (2012) [5], Nortoft & Gravesen (2013) [6], Qian & Sigmund (2011) [7], Cho & Ha (2009) [8], Lian et al (2013) [9], Qian (2010) [10], Li & Qian (2011) [11], where NURBS control points and/or weights have been used as design variables to control the boundary shape. On the other hand, in Kostas et al (2015) [12] and [13], due to the shape complexity of the ship hull, a geometric parametric model using high-level parameters with a direct design meaning has been developed and used for optimization purposes in the context of IGA approach.…”
Section: Introductionmentioning
confidence: 99%
“…In the papers [22,23,26] this method has been successfully applied to 2D shape optimization problems. The Winslow functional is minimized in Step 1 and the linearized Winslow functional is used in Step 2, except for [22] where quasi conformal deformation was used.…”
Section: If Any Of the Validity Constraints Inmentioning
confidence: 99%
“…[11,22,23,26]. Every time the geometry changes, that is, at every shape optimization iteration, one needs to update the parametrization in order to maintain the accuracy of the numerical approximation to the PDEs, governing the underlying physical model of the system.…”
Section: Introductionmentioning
confidence: 99%